2022
DOI: 10.1021/acsnano.2c08699
|View full text |Cite
|
Sign up to set email alerts
|

Bone ECM-like 3D Printing Scaffold with Liquid Crystalline and Viscoelastic Microenvironment for Bone Regeneration

Abstract: Implanting a 3D printing scaffold is an effective therapeutic strategy for personalized bone repair. As the key factor for the success of bone tissue engineering, the scaffold should provide an appropriate bone regeneration microenvironment and excellent mechanical properties. In fact, the most ideal osteogenic microenvironment is undoubtedly provided by natural bone extracellular matrix (ECM), which exhibits liquid crystalline and viscoelastic characteristics. However, mimicking a bone ECM-like microenvironme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…4 The bioactive scaffolds with an extracellular matrix (ECM)like microstructure composed of a porous and micro/ nanofibrous network have a superior ability to control cell behaviors such as cell adhesion and proliferation, which can facilitate scaffold-tissue integration. 5,6 Compared with a dense one, the ECM-mimicking scaffold allows proper oxygen/ nutrient delivery, tissue ingrowth, as well as neovascularization. 7 Electrospinning is the most versatile technology to fabricate a nanofibrous structure similar to natural ECM.…”
Section: Introductionmentioning
confidence: 99%
“…4 The bioactive scaffolds with an extracellular matrix (ECM)like microstructure composed of a porous and micro/ nanofibrous network have a superior ability to control cell behaviors such as cell adhesion and proliferation, which can facilitate scaffold-tissue integration. 5,6 Compared with a dense one, the ECM-mimicking scaffold allows proper oxygen/ nutrient delivery, tissue ingrowth, as well as neovascularization. 7 Electrospinning is the most versatile technology to fabricate a nanofibrous structure similar to natural ECM.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the HE immunohistochemical staining images (Figure a) that all of the scaffolds had good biocompatibility with the surrounding muscle tissue, and no serious inflammatory reaction was found around the scaffolds. In addition, cells near the scaffold were spindle shaped, which should be osteoid cells . Combined with the quantitative results in Figure d, it was shown that the osteoid areas of the four groups of scaffolds were relatively small on day 7, but the proportion of osteoid area in the N-PD-0.5Cu-LDHs group was slightly larger than that in other groups.…”
Section: Resultsmentioning
confidence: 63%
“…In addition, cells near the scaffold were spindle shaped, which should be osteoid cells. 57 Combined with the quantitative results in Figure 7d, it was shown that the osteoid areas of the four groups of scaffolds were relatively small on day 7, but the proportion of osteoid area in the N-PD-0.5Cu-LDHs group was slightly larger than that in other groups. On the 35th day, there was no significant change in the osteoid area on the PLLA scaffold group as compared to the seventh day.…”
Section: Ectopic Osteogenesis and Vascularizationmentioning
confidence: 55%
“…Their diameter changes were obtained by software analysis (Figure b), and the diameter of CNTs was 10.4 ± 2.4 nm and that of pCNTs was 16.5 ± 4.5 nm, which increased by 58.7% compared with that of unmodified CNTs, further indicating the effective modification of PDA. The surface elemental analysis of CNTs and pCNTs in Figure c revealed that the peaks of C 1s of CNTs were mainly 284.8 and 286.0 eV, respectively, corresponding to C–C and CO groups, respectively, while the subpeak of the C element appeared at 288.8 eV corresponding to the CO group due to the quinone groups of the PDA coat. The new N 1s peaks appeared at 298.4 and 399.4 eV due to the presence of primary and tertiary amino groups in PDA . The CO group in PDA also enhanced the signal intensity of the 1650 cm –1 peak in the FTIR spectra (Figure d) .…”
Section: Resultsmentioning
confidence: 97%